Brunei Malay. (22nd July 2016) - Deterding, David; Athirah, Ishamina
Abstract : Brunei Malay (ISO 639-3: kxd ) is spoken in the Sultanate of Brunei Darussalam and also in some nearby places in East Malaysia such as Miri and Limbang in Sarawak (Asmah2008 : 65), on the island of Labuan (Jaludin2003 : 35) and around Beaufort in western Sabah (Saidatul2003 ). Of the population of about 400, 000 in Brunei, about two-thirds are native speakers of Brunei Malay (Clynes2001 ), and the language is generally used as a lingua franca between the other ethnic groups (Martin1996 ), so even most Chinese Bruneians, numbering about 45, 000 (Dunseath1996 ), are reasonably proficient in Brunei Malay. Although Standard Malay is promoted as the national language of Brunei (Clynes & Deterding2011 ), in fact it is only used in formal situations, such as government speeches and television and radio broadcasts (Martin1996 ). The language that is spoken most extensively is Brunei Malay, though English is also widely used by the educated elite (Deterding & Salbrina 2013).